2007
DOI: 10.1510/icvts.2007.162669
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of peripheric cannulation after port-access surgery

Abstract: Several minimally invasive approaches, avoiding median sternotomy, have been described within the last few years for cardiac surgery. Femoral arterial and venous cannulation for extracorporeal perfusion are required for many of these operations. The aim of this report is to assess the long-term outcomes of femoral cannulations in patients who underwent minimally invasive procedures. One hundred and sixty patients underwent operations by the port-access method between January 2002 and October 2006. Cardiopulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Glower et al [1999] experienced minor or major complications after femoral cannulation in up to 10% of their patients who underwent port-access minimally invasive cardiac surgery. Other authors have reported rapid improvement of clinical symptoms, even in patients who experienced major complications after peripheral cannulation, such as major leg ischemia or local dissection [Sagbas 2007]. In our hands, 2 of the 4 complications noted were not observed at the side of introduction of the balloon endoocclusion catheter but at the contralateral side, which was cannulated with an additional arterial-perfusion cannula that was required for adequate CPB flow.…”
Section: Discussionsupporting
confidence: 42%
“…Glower et al [1999] experienced minor or major complications after femoral cannulation in up to 10% of their patients who underwent port-access minimally invasive cardiac surgery. Other authors have reported rapid improvement of clinical symptoms, even in patients who experienced major complications after peripheral cannulation, such as major leg ischemia or local dissection [Sagbas 2007]. In our hands, 2 of the 4 complications noted were not observed at the side of introduction of the balloon endoocclusion catheter but at the contralateral side, which was cannulated with an additional arterial-perfusion cannula that was required for adequate CPB flow.…”
Section: Discussionsupporting
confidence: 42%
“…Considering the growing number of indications for remote venous cannulation, which follows the development for small access open-heart surgery [16,17], as well as the growth of redo open-heart surgery [18,19], and other complex procedures [20,21], the advent of self-expanding venous cannulas is a major step forward in optimization of cardiopulmonary bypass. Better venous drainage with remote venous cannulation not only allows for higher pump flows and improved end-organ perfusion, but is also essential for a bloodless operative field, which in turn simplifies the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…No significant haemopericardium was found but the tip of the venous cannula was seen perforating the apex of the RV (Fig. 2) [1,2]. The routine use of TOE is likely to reduce the rate of more serious complications such as cardiac injury.…”
Section: Case Detailsmentioning
confidence: 99%